2015
DOI: 10.1002/nau.22760
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical botulinum toxin‐A injections reduce bladder pain of interstitial cystitis/bladder pain syndrome refractory to conventional treatment – A prospective, multicenter, randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Intravesical injections of 100 U of BoNT-A effectively reduced bladder pain symptoms in patients with IC/BPS. The adverse events were acceptable. Neurourol. Urodynam. 35:609-614, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 28 publications
(33 reference statements)
0
107
1
2
Order By: Relevance
“…Of the trials included, 4 reported BCG compared with placebo [32][33][34][35], 3 evaluated BoNTA in comparison with placebo [8,36,37], 2 reported RTX compared with placebo [38,39], 2 comparatively assessed chondroitin sulfate and placebo [7,40], 2 reported PPS compared with placebo [5,41], 1 evaluated lidocaine compared with placebo [42], 1 reported oxybutynin compared with placebo [43], and 1 assessed BCG in comparison with BoNTA [44]. The studies included assessed 905 patients in all.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the trials included, 4 reported BCG compared with placebo [32][33][34][35], 3 evaluated BoNTA in comparison with placebo [8,36,37], 2 reported RTX compared with placebo [38,39], 2 comparatively assessed chondroitin sulfate and placebo [7,40], 2 reported PPS compared with placebo [5,41], 1 evaluated lidocaine compared with placebo [42], 1 reported oxybutynin compared with placebo [43], and 1 assessed BCG in comparison with BoNTA [44]. The studies included assessed 905 patients in all.…”
Section: Resultsmentioning
confidence: 99%
“…One study had a three-arm design, and included 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [38]; another study had a four-arm design, and included 0.01 μM RTX, 0.05 μM RTX, 0.1 μM RTX, and placebo control groups [39]. Five studies identified additional treatments in both groups, including hydrodistention [8,37], oral PPS [5,41], and antibiotics [45]. The shortest and longest follow-up times were 29 days and 24 months respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the same efficacy, an increase in the dysuria and PVR were more frequent in patients who received 200 IU BoNT-A. In a double-blind, placebo-controlled, multicentre study, Kuo et al (38) compared the effects of hydrodistension + 100 IU BoNT-A injections versus hydrodistension + saline injections on 67 patients. On the postoperative eighth week, there was a significant decrease in VAS (−2.6 vs. −0.9, p=0.02) and an increase in MCC (+67.8 vs. −45.4, p=0.020) compared to the placebo group.…”
Section: -Interstitial Cystitis/bladder Pain Syndromementioning
confidence: 99%